Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/hsc.12550
|View full text |Cite
|
Sign up to set email alerts
|

Homeless people's experiences of medical respite care following acute hospitalisation in Denmark

Abstract: The aim of this study was to explore homeless people's health perspectives and experiences of a 2-week medical respite care programme following acute hospitalisation. There is a high level of health inequality when comparing the health status of homeless people to the general population, including increased mortality and morbidity. Homelessness predisposes an increased risk of infectious disease, cancer and chronic illness, such as diabetes and cardiovascular disease. Moreover, homeless people have a higher fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…Similar to research on the outcomes of medical respite or convalescent care programs that offer post-acute care to PWLEs following hospital discharge (Biederman et al, 2014;Pedersen et al, 2018), participants from both Program A and B identified the facilitation of rest and recovery until their health has stabilized enough to work on other goals as a strength. These programs, which support rest, recovery, and stabilization, offer a mechanism for continuity of care for PWLEs who would have otherwise been without a safe place to convalesce following hospital discharge.…”
Section: Discussionmentioning
confidence: 92%
“…Similar to research on the outcomes of medical respite or convalescent care programs that offer post-acute care to PWLEs following hospital discharge (Biederman et al, 2014;Pedersen et al, 2018), participants from both Program A and B identified the facilitation of rest and recovery until their health has stabilized enough to work on other goals as a strength. These programs, which support rest, recovery, and stabilization, offer a mechanism for continuity of care for PWLEs who would have otherwise been without a safe place to convalesce following hospital discharge.…”
Section: Discussionmentioning
confidence: 92%
“…At the same time, the intervention group had higher costs for general care services, rehabilitation, and treatment of substance abuse problems. One of the key results of the qualitative study by Pedersen et al, who studied the same respite care center, was that a post-hospital medical respite care stay allowed time for reflection on, for example, addiction problems [17]. It appears that some of the homeless people attended drug or alcohol therapy after the respite care stay.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, medical respite care enables cooperation with other social and health care services, such as primary care, social services, and outpatient medical care [14]. Staying in respite care and the improved opportunity to cooperate with municipalities seems to have a positive impact on substance abuse problems [15,17]. Thus, it seems likely that medical respite care for homeless people can be part of the solution to a complex problem.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the intervention group had higher costs for general care services, rehabilitation, and treatment of substance abuse problems. One of the key results of the qualitative study by Pedersen et al, who studied the same respite care center, was that a posthospital medical respite care stay allowed time for reflection on, for example, addiction problems (17). It appears that some of the homeless people attended drug or alcohol therapy after the respite care stay.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, medical respite care enables cooperation with other social and health care services, such as primary care, social services, and outpatient medical care (14). Staying in respite care and the improved opportunity to cooperate with municipalities seems to have a positive impact on substance abuse problems (17,18). Thus, it seems likely that medical respite care for homeless people can be part of the solution to a complex problem.…”
Section: Introductionmentioning
confidence: 99%